2014
DOI: 10.21608/jpp.2014.64707
|View full text |Cite
|
Sign up to set email alerts
|

Using Natural Alternative Fertilizers for Potato Production Under Sandy Soil Conditions in Egypt

Abstract: Two field experiments were carried out during the two successive seasons of 2010/2011 and 2011/2012 in the Farm of Agric. Res. Station, Wady El-Natrown Area, Fac. Agric. Cairo University, Egypt under saline water and sandy soil conditions. This investigation aimed to study the effect of compost, natural alternative fertilizers (rock phosphate and feldspar) combined with bacterial inoculation (Azotobacter spp and Azospirillum perna + B. megaterium + B. circulans) on yield, tubers quality and its component of (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 5 publications
4
9
0
Order By: Relevance
“…The results demonstrated that the concentration of N, P, and K in potato plants significantly (P<0.05) increased by 7.39, 6.08 and 30.91%, respectively, as a result of using bio fertilizers. Similar results were reported by Prajapati et al (2013) and Shehata et al (2014) who found that the N, P, and K concentrations were high in okra plants due to using biofertilizer. These increases might be due to the high activity of potassium dissolving bacteria which shows their ability to live zone rhizosphere at high number in the presence of the feldspar rock and/or converting of the unavailable forms of mineral nutrient to available forms (Hassan et al, 2006;Kandeel and Sharaf, 2003).…”
Section: Nitrogen Phosphorus and Potassium Concentration And Their supporting
confidence: 90%
“…The results demonstrated that the concentration of N, P, and K in potato plants significantly (P<0.05) increased by 7.39, 6.08 and 30.91%, respectively, as a result of using bio fertilizers. Similar results were reported by Prajapati et al (2013) and Shehata et al (2014) who found that the N, P, and K concentrations were high in okra plants due to using biofertilizer. These increases might be due to the high activity of potassium dissolving bacteria which shows their ability to live zone rhizosphere at high number in the presence of the feldspar rock and/or converting of the unavailable forms of mineral nutrient to available forms (Hassan et al, 2006;Kandeel and Sharaf, 2003).…”
Section: Nitrogen Phosphorus and Potassium Concentration And Their supporting
confidence: 90%
“…The obtained results recorded the closed similarity with those has been claimed by Abd-El- Salam and Shams (2012), Abd-El-Hakeem and Fekry (2014), Shehata et al, (2014). Beneficial effect of organic fertilizer on yield and its contents in expected to improve the physical, chemical conditions of soil and increase clustering.…”
Section: Yield and Its Componentssupporting
confidence: 85%
“…on sweet pepper and Abd-El-Hakeem and Fekry (2014) on sweet potato, they showed that the addition of K at 50 % potassium sulphate + 50% feldspar in combination with silicate dissolving bacteria gave the highest N,P and K content. Also, some recent reports showed that silicate dissolving bacteria played a promotion role in the release of Si, Fe and K from feldspar (Shehata et al, 2014;Abou El-Khair and Mohsen, 2016).…”
Section: -Chemical Constituentsmentioning
confidence: 99%
“…similarly, direct contact among microorganism and minerals can be essential in mineral alteration response, as microbial surfaces may be complicated with steel ions. a few recent reports showed that silicate dissolving bacteria performed a promotion function in the release of Si, Fe and K from feldspar (Labib et al, 2012 andShehata et al, 2014).…”
Section: Introdutionmentioning
confidence: 99%